2010
DOI: 10.1016/j.febslet.2010.11.038
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 suppresses oral squamous cell carcinoma motility by targeting ITGB1

Abstract: a b s t r a c tAlterations in the levels of molecules which interact with the extracellular matrix, such as integrins, are associated with invasion of oral squamous cell carcinomas (OSCC). The molecular mechanisms underlying dysregulation of integrin expression in OSCC, however, remain unclear. Here, we show that microRNA-124, a small non-coding RNA down-regulated in OSCC, is able to downregulate expression of integrin beta-1 (ITGB1) by interacting with its 3 0 untranslated region. Over-expression of miR-124 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 20 publications
9
104
1
Order By: Relevance
“…For instance, Stuart Hunt et al . found that miR‐124 suppressed OSCC motility by targeting ITGB1 39. Shiah et al .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Stuart Hunt et al . found that miR‐124 suppressed OSCC motility by targeting ITGB1 39. Shiah et al .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-124 is a brain-enriched miRNA that plays a crucial role in gastrulation and neural development (15,16), and its deregulation is related to carcinogenesis. The expression level of miR-124 is significantly decreased in glioma, medulloblastoma, oral squamous cell carcinoma, hepatocellular carcinoma, and bladder cancer, suggesting that it may function as a tumor suppressor (17)(18)(19)(20)(21)(22). However, its function in breast cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of miR-124 attenuated integrin beta-1(ITGB1) expression and suppressed the adherence and motility of oral squamous cancer cells [14]. To date, several lines of evidence have…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as one of the most abundantly expressed miRNAs in the central nervous system, miR-124 has been shown to play a significant role in the pathogenesis of various cancers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%